Macro Modeling Practices at Nepal Rastra Bank - Research Department, Nepal Rastra Bank (NRB Economic Review, 2018)
This paper presents a brief survey of macroeconomic models of Nepal. It also empirically investigates sectoral models of macroeconomic variables including inflation, monetary aggregate, fiscal and external sector upon which policymakers' concern rests during the process of monetary policy formulation. Sample period of 1975 to 2016 is used for the estimation. The Data Generating Process (DGP) identified in this paper for the variables of interest meets necessary criteria both from theory and empirical ground. These models are useful to understand general relationship from sectoral perspective and to carryout simple forecasting for making monetary and other macroeconomic policy decisions.